Українська народна сакральна скульптура в контексті зв’язків із західними сусідами - Моздир, М. (Інститут народознавства НАН України, 2008)
Folk sacral sculptures, as “figures”, roadside and memorial crosses, boundary and memorial monuments etc. Belong to a king of folk artistic creativeness, wide-spread in Ukraine since XVI c. Western European sources of its subjects. Negative attitude of Russian Orthodox Church and state authorities to this sculpture Demolishing of artifacts in the years of Soviet regime. The most known centers of production (Demnia, Stare Misto, Narayiv) and artists (V.Bidula, V.Bilynsky). Revival of this kind of folk artistry under condition of independent Ukraine.